Mother-to-infant emotional involvement at birth - Figueiredo, Bárbara (2009)
Objectives. To study mother-to-infant emotional involvement at birth, namely factors (socio-demographics, previous life events, type of delivery, pain at childbirth, support from partner, infant characteristics, early experiences with the newborn, and mother’s mood) that interfere with the mother’s positive, negative and not clear emotions toward the newborn. Methods. The Bonding Scale (an extended Portuguese version of the ‘New Mother-to-Infant Bonding Scale’) and the Edinburgh Postnatal Depression Scale were administrated during the first after delivery days to 315 mothers recruited at Ju´lio Dinis Maternity Hospital (MJD, Porto, Portugal). Results. A worse emotional involvement with the newborn was observed when the mother was unemployed, unmarried, had less than grade 9, previous obstetrical/psychological problems or was depressed, as well as when the infant was female, had neonatal problems or was admitted in the intensive care unit. Lower total bonding results were significantly predicted when the mother was depressed and had a lower educational level; being depressed, unemployed and single predicted more negative emotions toward the infant as well. No significant differences in the mother-to-infant emotional involvement were obtained for events related to childbirth, such as type of delivery, pain and partner support, or early experiences with the newborn; these events do not predict mother’s bonding results either. Conclusion. The study results support the need for screening and supporting depressed, unemployed and single mothers, in order to prevent bonding difficulties with the newborn at birth.